2011
DOI: 10.1007/s00268-011-1204-6
|View full text |Cite
|
Sign up to set email alerts
|

Predicting Distant Metastasis in Patients With Suspected Pancreatic and Periampullary Tumors for Selective Use of Staging Laparoscopy

Abstract: In patients with a suspected pancreatic or periampullary tumor, the tumor size, weight loss, and jaundice are key predictors of metastasis at exploration. SL might be beneficial in patients with a tumor ≥3 cm and severe weight loss and in those with a tumor ≥4 cm and moderate weight loss.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
21
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(23 citation statements)
references
References 46 publications
2
21
0
Order By: Relevance
“…Although resection rates have increased along with increasing centralization of pancreatic surgery in the Netherlands, a radical resection is deemed impossible in a considerable proportion of patients who undergo surgical exploration. The present nationwide results are largely in line with earlier institutional reports, showing that 12–22 per cent of patients who undergo surgical exploration for pancreatic cancer do not have tumour resection because of metastatic disease, and 6–26 per cent because of unresectable M0 (locally advanced) disease. The present study also shows that an increased surgical exploration rate over time paralleled an increased resection rate, mostly owing to a decrease in unresectable M0 disease detected at exploration.…”
Section: Discussionsupporting
confidence: 91%
“…Although resection rates have increased along with increasing centralization of pancreatic surgery in the Netherlands, a radical resection is deemed impossible in a considerable proportion of patients who undergo surgical exploration. The present nationwide results are largely in line with earlier institutional reports, showing that 12–22 per cent of patients who undergo surgical exploration for pancreatic cancer do not have tumour resection because of metastatic disease, and 6–26 per cent because of unresectable M0 (locally advanced) disease. The present study also shows that an increased surgical exploration rate over time paralleled an increased resection rate, mostly owing to a decrease in unresectable M0 disease detected at exploration.…”
Section: Discussionsupporting
confidence: 91%
“…Historically, the answer to the patient’s question about the possibility of such an event happening is based on the surgeon’s anecdotal experience and may vary from 5% to 25%. Previous studies have reported that approximately 11% to 24% of patients with radiologically resectable PDAC are found to have OMD at exploration . However, the probability of OMD in patients with PDAC in the era of enhanced imaging remains practically unknown.…”
Section: Introductionmentioning
confidence: 99%
“…Preoperative imaging was more extensive in these studies. So far, only two studies have shown any factors (i.e., Blumgart T-stage) that increase the diagnostic yield in these patients [7, 13], whereas several other predictors (e.g., CA19-9, tumor size) of unresectable disease at SL have been identified and validated for pancreatic cancer patients [1823]. …”
Section: Discussionmentioning
confidence: 99%